Pengaruh Kompetensi, Pelatihan Dan Lingkungan Kerja Fisik Terhadap Kinerja Karyawan Pt. Toyota Logistra Pingloka Indonesia Cikarang Timur - Retno Purwani , Setyaningrum; Robi Habibi (STIE AMKOP, 2022)
This study discusses whether competence, training and physical work environment affect the performance of employees of PT. Toyota Logistra Pingloka Indonesia. The purpose of this study was to examine the effect of competence, training and physical work environment on the performance of employees of PT. Toyota Logistra Pingloka Indonesia.This sampling technique uses the slovin formula and obtained as many as 122 people who are employees of PT. Toyota Logistra Pingloka Indonesia. The data obtained were analyzed quantitatively using analytical tools in the form of validity test tables, reliability tests, classical assumption tests, model feasibility tests, hypothesis testing, testing to determine the effective and relative contribution using the SPSS 24 for Windows application program.The results of statistical analysis partially show that competence, training and physical work environment have a positive and significant effect on performance. Judging from the significance value of the competency T test (X1) of 0.000 and training (X2) of 0.008, while the physical work environment (X3) is 0.000. Simultaneous statistical analysis results show that competence, training and physical work environment have a significant effect on performance simultaneously. Judging from the significance value of the F test of 0.000 and the R Square value of 0.629 or 62.9% while 31.1% is influenced by other variables not examined in this study. Keywords: competence, training, physical work environment, employee performance